How Hope Strengthens Mental Emotionality as A Mediator of the Link Between Social Support and Psychosocial Adjustment in People Living With HIV - Nasir, Abd; Sulaiman, Nur Adibah Binti Solihin; Latif, Rusnani Ab; Maruf, Anwar; Goenharto, Sianiwati; Fadhillah, Harif; ., Rohman; Harianto, Susilo; Huda, Nuh; Sari, Amillia Kartika; Wesprimawati, Irma (Journal of Posthumanism, 2025)
Background - Psychological problems due to mental stress in the environment experienced by people living with HIV make them have difficulty in adjusting both psychologically and socially. Objective - This study aims to determine the role of hope as a mediator of the relationship between social support and psychosocial adjustment in PLWHA. Method - Based on a cross-sectional analysis, we recruited 154 HIV patients. Data were collected using convenience sampling techniques, and Andrew F. Hayes's PROCESS v3.4 macro in SPSS was used to analyze this study. Results - This study shows that Hope fully mediates the relationship between social support and psychosocial adjustment ability (βc = 0.3997; **p = <0.001). Implications - This suggests that social support will be meaningful if it is adjusted to the expectations set so that it can be used as a source of mental resilience to improve psychosocial adjustment ability.